2016
DOI: 10.2308/ciia-51650
|View full text |Cite
|
Sign up to set email alerts
|

Why Audit Committees Oppose Mandatory Audit Firm Rotation: Interview Evidence from Canada

Abstract: SUMMARY:This article summarizes our recent study (Fontaine, Khemakhem, and Herda 2016), which investigates audit committee (AC) members' perspectives on mandatory audit firm rotation (MAFR), mandatory audit partner rotation, ways in which AC members monitor auditor independence, and the costs associated with changing audit firms. We conduct in-person interviews with AC members in Canada to explore our research questions. Our findings reveal that AC members view MAFR as an unnecessary threat to their shareholde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
3
1
Order By: Relevance
“…As discussed in Section 5.2 and iterated by the discriminate analysis, both groups do not believe that MAFR is necessary and doubt its effectiveness. These results are contrary to Hussey and Lan (2001), who found that UK-based CFOs are more optimistic about MAFR and support more recent findings on audit committees' views on MAFR by Fontaine et al (2017).…”
Section: Differences Between Auditors and Non-auditorscontrasting
confidence: 51%
See 2 more Smart Citations
“…As discussed in Section 5.2 and iterated by the discriminate analysis, both groups do not believe that MAFR is necessary and doubt its effectiveness. These results are contrary to Hussey and Lan (2001), who found that UK-based CFOs are more optimistic about MAFR and support more recent findings on audit committees' views on MAFR by Fontaine et al (2017).…”
Section: Differences Between Auditors and Non-auditorscontrasting
confidence: 51%
“…Our findings show that key decision-makers, across various roles in the audit industry, do not generally believe quality will be improved and the regulation will have unintended consequences. At the client level, consistent with Fontaine et al (2017) and Williams and Wilder (2016), preparers were concerned about the additional time and resources expended to engage with auditors who would be unfamiliar with the intricacies of their business model. Similarly, audit committees believed that the cost of implementing MAFR would be material and unnecessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interviewees were provided with the script before the interview so that they had the opportunity to think about the questions that would be raised (Hermanson et al, 2012). The number of interviewees is similar to Nath et al (2020), with 15 interviews and slightly fewer than the Sormunen (2014), Fontaine et al (2017), Segal (2019) and Fontaine et al (2013), with 18, 19, 20 and 20 interviews, respectively, all within the audit field. We considered 14 interviews to be sufficient, as we have designed the script with the input of four additional partners who agreed on the topics to be covered.…”
Section: Methodsmentioning
confidence: 99%